EFEKTIVITAS PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT DI KECAMATAN BANJARWANGI KABUPATEN GARUT - Indah Aqilah Febriani; Muhammad Khainur Fahlawi; Menara Yosua Parluhutan (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2021)
Pembatasan pemberlakuan kegiatan masyarakat is one of the government's programs in tackling and breaking the chain of covid-19 spread that continues to grow in Indonesia. Covid-19 is rapidly developing and becoming a global issue that impacts all lives in different countries. This makes the government both central and village level must think about various strategies in an effort to prevent its spread. In addition to strategic from the government, participation from the community is also indispensable in efforts to prevent its spread. In addition, we also found participation from the people of Kecamatan Banjarwangi, Kabupaten Garut who participated in the prevention of Covid-19 by implementing policies that have been set by the government. The purpose of this research is to know in detail the form of community participation in the handling of Covid-19 in Kecamatan Banjarwangi, Kabupaten Garut. The research method is descriptive and uses qualitative methods. Meanwhile, for data collection is used library studies derived from data sources derived from scientific journals, book literature, and official websites that are then described through analysis that describes the application of government policies, namely with Pembatasan pemberlakuan kegiatan masyarakat (PPKM) in the response to the Covid-19 pandemic outbreak in Kecamatan Banjarwangi, Kabupaten Garut. The results of this study explain that the application of government policies through PPKM in the district of Banjarwangi, Garut includes participation in planning, participation in the implementation, with the use of masks when traveling, restrictions on community activities without clear purpose, and restrictions on the operating hours of vehicle activities and business activities (shops). The implementation of PPKM activities in countering the Covid-19 pandemic in Kecamatan Banjarwangi, Kabupaten Garut seems to have been running effectively. With the involvement of the village community is very petrified this government program in tackling Covid-19, because the villagers are very understanding of the situation and conditions of the community in the environment. After the involvement of other agencies such as the TNI / POLRI is also very helpful smoothly this program with the creation of security and order during the activities. The purpose of restrictions on the implementation of community activities is to suppress and stop the positive number of Covid-19 in Kecamatan Banjarwangi, Kabupaten Garut. Keywords: Effectiveness: Restrictions on Community Activities; Kabupaten Garut